Competence profiles update and impacts for the future digital society: an European perspective - Capogna, Stefania; Scarozza, Danila (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
The essay aims to reconstruct the European perspective concerning the development trends determined by the digital revolution and its outcomes at work in terms of new profiles, skills and risk categories that are prefigured for citizenship at all ages. The essay focuses on digital competence for young people, digital competence at work and digital competence for active citizenship, starting from the European policies and strategies about digitisation. The essay concludes with a critical reflection on the need to move away from a “reactive mode” and adopt a “proactive position” to govern the digital revolution by promoting people’s active and co-responsible participation. A critical issue for governing any society lies in its founding values. Hence, there is a need to ask critical questions about values, ethics and social justice, and to move beyond technological determinism.